Sustaining middle-classness: studying the lives of Indian working mothers and their children in Malaysia / Sally Anne Malar Paramanathan - Sally Anne Malar, Paramanathan (2016)
The focus of this study is middle-class Indian women in Malaysia; those who are mothers, are educated, and who hold professional jobs. This thesis explores the ways in which middle-class Indian mothers in Malaysia struggle to have an identity. These women have the achievements necessary for a national identity of successful working motherhood. But in reality, there are obstacles that debilitate their self-actualisation. This thesis also takes a look at the lives of the children of these mothers in an introductory manner. The children's lives are juxtaposed alongside that of their mothers, and their navigation of life is also accounted for. Through the use of a qualitative methodology, the finding chapters looked at how Education, Time, and Work Experience affect the lives of these mothers and their children. It is found that children’s education is crucial in the lives of middle-class Indians and they do all that they can to ensure their children do well in school. Middle-class values continue to remain entrenched through the monolith role of education. Furthermore, how the mothers and children manage time is examined and it is found that strict adherence to time-tables and schedules evidence a middle-class lifestyle for these mothers. Following that, the mothers’ working experience is explored, together with the children’s opinion on it. In talking about the challenges of paid employment, they raised the issue of discrimination based on hierarchical patriarchy and ethnicity. However, the pressures from their personal and private lives were often the more prominent. In the concluding chapter, the discussion on whether these mothers are able to sustain middle-class values is brought to a close. It is found that a certain degree of empowerment is achieved, but there are still areas of inequality to contend with.